Nicotiana Occidentalis Chloroplast Ultrastructure imaged with Transmission Electron Microscopes Working at Different Accelerating Voltages - Svidenská, Silvie (Jihočeská univerzita, 2010)
The main goal of this thesis is to study and compare electron microscopy images of Nicotiana Occidentalis chloroplasts, obtained from two types of transmission electron microscopes,which work with different accelerating voltage of 80kV and 5kV. The two instruments, TEM JEOL 1010 and low voltage electron microscope LVEM5 are employed for experiments. In the first theoretical part, principle of electron microscopy and chloroplast morphology is described. In experimental part, electron microscopy images of chloroplast under different conditions of sample preparation are shown and discussed.
Nicotiana Occidentalis Chloroplast Ultrastructure imaged with Transmission Electron Microscopes Working at Different Accelerating Voltages
Keywords: LVEM5; LVTEM; Chloroplast; Nicotiana Occidentalis; TEM JEOL 1010; příprava vzorků pro transmisní elektronový mikroskop.; LVEM5; LVTEM; Chloroplast; Nicotiana Occidentalis; TEM JEOL 1010; preparation of samples for transmission electron microscope.